Two halves of a whole. (2nd September 2019) - Long, Kim; Francis, Nadine
Abstract : What is it like to work so closely and for so long with a colleague that you cannot imagine being without them? Dental nurses and reception teamKim Long andNadine Francis reveal the secret of being a good 'wingman'